The Book of Peace : By Christine de Pizan - Christine, de Pisan, ca. 1364-ca. 1431 (Book collections on Project MUSE., 2008)
"An English translation of The Book of Peace, written between 1412 and 1414 by Christine de Pizan, one of the earliest known women authors. Translated material is side by side with the original French text"--Provided by publisher.